New York Paper - Treatment Tests on Ores of Consolidated Coppermines Co. (with Discussion) - Robert Linton (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1921)
In 1898, Joseph L. Giroux and J. A. Snedaker organized the Pilot Knob Copper Co. and began developing the Pilot Knob mine at Kim-berly, Nev., for high-grade copper ores, carrying good gold and silver values, that the formation had disclosed. At that time the nearest railroad was over 150 mi. distant. The high-grade ores did not prove to be extensive at this point—at least to the depth (240 ft.) to which the work was carried—but development of neighboring claims indicated extensive deposits of sulfide porphyry ore of concentrating grade lying at shallow depth, and deeper deposits of direct-smelting oxidized ores occurring in limestone near the limestone-porphyry contact. The properties passed through the hands of several organizations, with only meager development, until acquired in 1913 by Consolidated Coppermines Co., whose holdings now comprise 3480 acres of mining claims in the Robinson district. Since that time development has been prosecuted more actively; and for the purpose of determining the most efficient and economical method of treating the ores, considerable testing work has been done during the past three years, both in the laboratory and in actual mill operations. At first, the shipments were of ore high enough in grade to be profitable even with the long wagon hauls to the railroad and prevailing freight and smelting charges. In 1905, a blast furnace and a concentrator were erected at Kimberly. On account of insufficient ore supply, the blast furnace was never blown in and later was dismantled. The concentrator as originally equipped was operated for only about two months, both because the ore supply at that time was not sufficient and because gravity concentration did not yield satisfactory extraction. The location and arrangement of the mill further entailed high operating costs. In 1908, the Nevada Consolidated Copper Co. began to mill successfully, on a large scale, its sulfide porphyry ores, which are similar in character to the adjacent Coppermines ores. After that time, all of the ores and concentrates produced by Coppermines Company were smelted and a considerable part of the Coppermines low-grade ores concentrated at the Steptoe works of the Nevada Consolidated Co.